Culturally safe communication and the power of language in Arctic nursing - Møller, Helle (Études/Inuit/Studies, 2016)
Nursing education and healthcare in Nunavut and Greenland have been developed, and to a large degree governed, by Danish and Euro-Canadian norms, culture, and language. Teachers and healthcare professionals are mostly Danish-speaking Danes in Greenland and English-speaking Euro-Canadians from southern Canada in Nunavut. This is not trivial for Greenlandic and Canadian Inuit nursing students or nurses, or for Canadian and Greenlandic Inuit healthcare recipients, the majority of whom speak Greenlandic or Inuktitut as their mother tongue. Drawing primarily on data from interviews with Canadian and Greenlandic Inuit nurses and nursing students between 2007 and 2010, I discuss the ways in which language as habitus may work to support or impede culturally safe care, workplaces, and education. I argue that the double-cultured Greenlandic and Canadian Inuit nurses and nursing students are invaluable to Arctic healthcare systems as culturally safe healthcare providers and habitus brokers. Furthermore, healthcare professionals from outside Greenland and Nunavut can advantageously learn from their Greenlandic and Canadian Inuit counterparts.